MMC Based Super Capacitor and Battery Hybrid Energy Storage System and Hybrid Synchronous Control Strategy - Yu CAO; Pengfei HU; Wanqi CAI; Xi WANG; Daozhuo JIANG; Yiqiao LIANG (Zhongguo dianli)
To meet the requirements of energy storage system to provide inertia and primary frequency regulation for centralized configuration and optimal control of multiple energy storage media, an overall hybrid synchronous control (HSC) strategy is proposed for modular multilevel converter (MMC) based hybrid energy storage system (HESS). The modular design method is adopted for MMC-HESS, where the super capacitors (SC) and batteries are placed in the DC bus side and in the sub-module (SM) respectively, which has advantages of high power density and high energy density. The topology and working principle of HESS are analyzed, and the HSC strategy is used to provide system inertia and primary frequency regulation, as well as the synchronization capability and isolation control function for fault current limiting. The filter is employed for distributing power of energy storage, and the state of charge (SOC) balancing control is used for battery energy regulation. Finally, based on the hardware-in-the-loop experimentation platform, the MMC-HESS topology and control strategy proposed in this paper are verified. The experimental results indicate that the proposed HSC-MMC-HESS is able to provide inertia and frequency support capability, and switch flexibly between fault current-limiting, normal grid-connection and island operation, giving a full play to the comprehensive advantages of hybrid energy storage. The application of HSC-MMC-HESS has good prospects in medium-voltage distribution network.